2020
DOI: 10.5435/jaaos-d-19-00245
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Residents' Transfer of Knee Arthroscopic Abilities from the Simulator to the Operating Room

Abstract: Introduction: The ultimate goal for any surgical simulation program is to prove the capability of transferring the skills learned to real-life surgical scenarios. We designed an arthroscopic partial meniscectomy (APM) training program and sought to determine its ability to transfer skills to real patients. Methods: Eleven junior orthopaedic residents and three expert knee surgeons were included. A low-fidelity knee simulator was used. Trainees had two b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…The descriptive characteristics of the included studies are listed in Table 1 . The majority of arthroscopic skills testing was performed in simulated environments, including a simulator [ 21–38 ], cadaver [ 33 , 37 , 39–44 ] and animal model [ 45 ], and five studies [ 32 , 38 , 46–48 ] were performed on patients. Of the included studies, participants mainly involved medical students, orthopaedic residents, surgeons and experts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive characteristics of the included studies are listed in Table 1 . The majority of arthroscopic skills testing was performed in simulated environments, including a simulator [ 21–38 ], cadaver [ 33 , 37 , 39–44 ] and animal model [ 45 ], and five studies [ 32 , 38 , 46–48 ] were performed on patients. Of the included studies, participants mainly involved medical students, orthopaedic residents, surgeons and experts.…”
Section: Resultsmentioning
confidence: 99%
“…Six types of GRS were reported in the eligible studies, and an Injury Grading Index Performance Scale (IGI)[ 42 ] fulfilled the inclusion criteria. The most commonly used GRS for assessment was the Arthroscopic Surgical Skill Evaluation Tool (10 studies) [ 32 , 33 , 36–40 , 43 , 45 , 46 ], followed by Basic Arthroscopy Knee Skill Scoring System (three studies) [ 21 , 35 , 44 ] and the other GRS were reported only in one study each [ 26 , 33 , 41 , 48 ]. Descriptions of studies using checklists or GRS are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Simulation, and meta-analysis of simulation, has been carried out in other aspects of cardiothoracic surgery, for example, bronchoscopy 3 , 12 . Simulation has also shown to be useful in real-life scenarios, with a study by Ledermann and co-workers evaluating junior orthopaedic residents, demonstrating that when trainees use a low-fidelity simulator to perform an arthroscopic partial meniscectomy, their score in the Arthroscopic Surgical Skill Evaluation Tool improved in real-life patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Diferentes laboratorios de habilidades quirúrgicas desarrollados en distintas instituciones han tenido resultados positivos en la formación de especialistas. 9,10 En el caso de Ortopedia y Traumatología, el rol de la simulación como forma de aprendizaje tiene cada vez mayor evidencia, [11][12][13][14] siendo particularmente relevante para los residentes jóvenes quienes muchas veces no se sienten cómodos en el escenario real o tienen poco acceso a estos escenarios para desarrollar sus competencias. 15,16 Con el propósito de disminuir los riesgos dentro del pabellón y asegurar un aprendizaje de competencias prácticas, nacen los programas intensivos de adquisición de habilidades básicas.…”
Section: Wwwmedigraphicorgmxunclassified